2021
DOI: 10.1111/febs.16183
|View full text |Cite
|
Sign up to set email alerts
|

Migrasome biogenesis and functions

Abstract: The migrasome is a newly discovered organelle produced by migrating cells. As cells migrate, long and thin retraction fibers are left in their wake. On these fibers, we discovered the production of a pomegranate-like structure, which we named migrasomes. The production of migrasomes is highly correlated with the migration of cells. Currently, it has been demonstrated the migrasomes exhibit three modes of action: release of signaling molecules through rupturing or leaking, carriers of damaged mitochondria, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 18 publications
2
56
0
Order By: Relevance
“…The transporting mechanisms of damaged mitochondria to migrasomes are relatively clear [ 6 ]. Nevertheless, the origin of small vesicles inside migrasomes and the sorting and transporting mechanisms of these small vesicles, nucleic acids, and proteins into migrasomes remain to be identified [ 1 , 4 , 67 , 109 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transporting mechanisms of damaged mitochondria to migrasomes are relatively clear [ 6 ]. Nevertheless, the origin of small vesicles inside migrasomes and the sorting and transporting mechanisms of these small vesicles, nucleic acids, and proteins into migrasomes remain to be identified [ 1 , 4 , 67 , 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jiao et al found that migrasomes were extensively generated by circulating neutrophils in mice, as that around 87% of migrasomes from blood originated from neutrophils [ 6 ]. Some neutrophil-derived migrasomes can adhere to vessels in the circulation for a long time, while some are detached quickly after generation [ 66 , 67 ]. Most importantly, the migrasomes generated by neutrophils contain damaged mitochondria [ 6 ].…”
Section: The Current Understanding Of the Biological Functions Of Mig...mentioning
confidence: 99%
See 1 more Smart Citation
“…Migrasomes are short-lived structures that rupture soon after their formation and release their content of signaling molecules to orientate the migration of following cells (Jiang et al, 2019). Migrasomes can also be internalized by surrounding cells and thereby transfer regulatory factors they contain to modulate recipient cells fate (Jiang et al, 2019; Yu & Yu, 2021). While it is proven that fibroblasts can produce migrasomes, it is not clear whether these structures may participate in orienting cancer cell migration.…”
Section: Main Textmentioning
confidence: 99%
“…Thus, while it is technically possible to isolate migrasomes from developmental organisms, there is room for improvement. Future studies will also need to establish quality controls to ensure migrasomes specifically are being enriched for further study [ 22 ].…”
Section: Analyzing Extracellular Vesicles and Protrusions In Developmentmentioning
confidence: 99%